Ordbog over det norrøne prosasprog som en historisk ordbog - Sanders, Christopher (LexicoNordica, 2006)
This article aims to place Ordbog over det norrøne prosasprog (ONP) within the context of the discussion of just how historical various so-called “historical dictionaries” are or aim to be. The principal focus for ONP is the order in which the senses of polysemous words are presented. The abstract noun dyggð (‘virtue’) is chosen to demonstrate both what is typical and what is perhaps peculiar to ONP in this respect.